Imaging, spectroscopy and manipulation of C60 molecules on semiconductor surfaces - Chiutu, Cristina (2013)
Scanning probe microscopy techniques were employed to investigate C60 molecules adsorbed on Si(111)-(7x7) and Ag-Si(111)-(√3x√3)R30o using imaging, spectroscopy, and manipulation methods. First, dynamic scanning tunnelling microscopy revealed the lowest unoccupied molecular orbital features of C60 molecules adsorbed on Si(111)-(7x7) with extremely high resolution at 77 K. Experimental data were compared with Hückel molecular orbital theory simulations to determine the orientation of the molecules on these surfaces. Second, C60 molecules were imaged with a qPlus atomic force microscope, in the attractive force regime and appeared as bright spherical protrusions. The potential energy of interaction between the AFM tip and C60 molecules adsorbed on Si(111)-(7x7) was quantified by force spectroscopy. Furthermore, a C60 molecule was transferred to the scanning probe microscope tip and used as molecular probe to image the Si(111)-(7x7) surface and other C60 molecules. The on-tip C60 molecule was imaged with high precision. Hückel molecular orbital theory calculations accurately predicted the shape and characteristics of molecular orbitals observed with dynamic scanning tunnelling microscopy, which were strongly dependent on molecular symmetry, orientation, and adsorption angle. Using qPlus atomic force microscopy, chemical reactivity was probed close to or at the carbon atom positions in the C60 cage. Density functional theory simulations showed that an (iono)covalent bond formed between a carbon atom and the underlying Si adatom was responsible for contrast formation. The pair potential for two C60 molecules was also determined experimentally and found to be in very good agreement with the Girifalco potential (Girifalco, L.A., J. Phys. Chem., 1992. 96(2): p. 858). Using Hückel molecular orbital theory, the mutual orientation of a C60 molecule adsorbed on the STM/AFM tip and a C60 molecule adsorbed on the Si(111)-(7x7) surface was determined via comparison of simulated images to the experimental data. Individual C60 molecules were also manipulated with qPlus atomic force microscopy. Manipulation of single C60 molecules was performed on the Ag-Si(111)-(√3x√3)R30o surface using scanning tunnelling microscopy at room temperature and at 100 K. The interaction was predominantly attractive. Due to weak molecule-substrate interaction, a short-range chemical force between the C60 molecule and the tip was considered to be responsible for the manipulation process.